Answers

The Brainliest Answer!
2016-07-16T23:03:10+08:00
To get the common difference,

2x - 6 = x - 7 + (2-1)d
2x - 6 = x - 7 + d
2x - x - 6 + 7 = d
x + 1 = d

Therefore, the common difference is x + 1

Let's check...

2x - 6 = x - 7 + d
2x - 6 = x - 7 + (x + 1)
2x - 6 = 2x -6
1 5 1
  • Brainly User
2016-07-17T06:47:34+08:00
Find the difference between the two expression.  Apply the rule in subtraction of polynomials:

Common difference: a₂ - a₁

    2x - 6   (a₁)  
 - ( x - 7)  (a₂)   Change the sign of each term of subtrahend
------------------ 
    x + 1   common difference
    
0